Allogeneic Bone Marrow‐Derived Mesenchymal Stromal Cells Expanded In Vitro for Treatment of Aplastic Anemia: A Multicenter Phase II Trial. (15th May 2017) - Pang, Yan; Xiao, Hao‐Wen; Zhang, Hang; Liu, Zeng‐Hui; Li, Li; Gao, Yang; Li, Hong‐Bo; Jiang, Zu‐Jun; Tan, Huo; Lin, Jing‐Ren; Du, Xin; Weng, Jian‐Yu; et al.
Abstract: We conducted a phase II, noncomparative, multicenter study to assess the efficacy and safety of allogeneic bone marrow‐derived mesenchymal stromal cells (BM‐MSCs) expanded in vitro for patients with aplastic anemia (AA) refractory to immunosuppressive therapy. Seventy‐four patients from seven centers received allogeneic BM‐MSCs at a dose of 1–2 × 10 6 cells/kg per week for 4 weeks. Responses were assessed at 0.5, 1, 2, 3, 6, 9, and 12 months after the first cells infusion. Patients with response at 1 month continued to receive four infusions. All patients were evaluable. The overall response rate was 28.4% (95% confidence interval, 19%–40%), with 6.8% complete response and 21.6% partial response. The median times to response of leukocytic, erythrocytic, and megakaryocytic linages were 19 (range, 11–29), 17 (range, 12–25), and 31 (range, 26–84) days, respectively. After median follow‐up of 17 months, overall survival was 87.8%. Seven patients developed transitory and mild headache and fever, but no other adverse events were observed. Antithymocyte globulin used in previous treatment and no activated infection throughout treatment were predictors for response. Allogeneic BM‐MSCs infusion is a feasible and effective treatment option for refractory AA. The trial was registered atwww.clinicaltrials.gov as NCT00195624. Stem Cells Translational Medicine 2017;6:1569–1575 Abstract : Bone marrow cellularity at baseline and at 12 months in a patient with trilineage responses to BM‐MSCs.